2021
DOI: 10.1039/d1ta04104e
|View full text |Cite
|
Sign up to set email alerts
|

Metal phosphides: topical advances in the design of supercapacitors

Abstract: World-wide increased energy consumption and demand has aimed our prime requisites of high-energy storage systems with longer life. Hence, research and development on supercapacitors based on efficient and robust electrode...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 200 publications
0
50
0
Order By: Relevance
“…High endurance to long-term charge–discharge is a prerequisite of the working electrode to be used for real supercapacitor operations. Since the cyclic stability of redox-active materials is not as good as EDLC, the use of MWCNT as a skeleton is believed to strengthen the mechanical integrity of the hybridized electrode Figure d shows the retention plot as a function of cycle numbers for the Co 2 P 2 O 7 /MWCNT electrode where the specific capacity equivalent to a 100% retention corresponds to the value achieved in the first GCD cycle of the stability test conducted for a constant current density of 3.5 A g –1 , which is 153.8 mA h g –1 (261.5 μA h cm –2 ).…”
Section: Resultsmentioning
confidence: 73%
“…High endurance to long-term charge–discharge is a prerequisite of the working electrode to be used for real supercapacitor operations. Since the cyclic stability of redox-active materials is not as good as EDLC, the use of MWCNT as a skeleton is believed to strengthen the mechanical integrity of the hybridized electrode Figure d shows the retention plot as a function of cycle numbers for the Co 2 P 2 O 7 /MWCNT electrode where the specific capacity equivalent to a 100% retention corresponds to the value achieved in the first GCD cycle of the stability test conducted for a constant current density of 3.5 A g –1 , which is 153.8 mA h g –1 (261.5 μA h cm –2 ).…”
Section: Resultsmentioning
confidence: 73%
“…The CV curves of C 1 , MC 2 , MC 4 , and MC 6 electrodes showed redox peaks at all scan rates prominently indicating pseudocapacitor like response material [40,41] . Despite this, CV profiles aren′t exactly rectangular, indicating quasi‐ideal capacitive/ pseudocapacitor behaviour.…”
Section: Resultsmentioning
confidence: 97%
“…In order to determine the total charge stored by any electrode, there are two major factors that must be considered: surface capacitive and diffusion‐controlled processes. The surface‐controlled kinetics includes non‐faradic charge storage in the EDL, and diffusion kinetics involves highly localized faradic electron transfer reactions at the electrode surface [40,41] . Complete analysis of dynamics was calculated based on power law to quantify their relative contribution as shown in equation (2) [41,42] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the redox reaction mechanism of nickel phosphides in an aqueous solution [29][30][31][32][33]; however, there is still no solid consensus as to the redox reaction mechanism of nickel phosphides in an aqueous solution, except for the active participation of hydroxyl ions in the reaction. It is suggested that the following irreversible (Equation ( 5)) and reversible (Equation ( 6)) reactions take place when nickel phosphides are in an alkaline solution.…”
Section: Electrochemical Testsmentioning
confidence: 99%